2016
DOI: 10.1016/j.jjcc.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

High-dose statin therapy with rosuvastatin reduces small dense LDL and MDA-LDL: The Standard versus high-dose therApy with Rosuvastatin for lipiD lowering (SARD) trial

Abstract: High-dose statin therapy significantly reduced the sd-LDL and MDA-LDL components of atherosclerotic lipoproteins without adverse events in comparison with low-dose statin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
(22 reference statements)
2
19
0
Order By: Relevance
“…1 , the lipid-lowering therapies such as atorvastatin 20 mg/d plus ezetimibe 10 mg/d and atorvastatin 40 mg/d were compared in the aspect of lipid-lowering efficacy. The lipid-lowering efficacy of both strategies was in accordance with the results reported in previous studies [ 9 11 ]. Abundant evidences demonstrated that the lower the level of LDL-C reached, the better the reduction of cardiovascular events [ 12 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…1 , the lipid-lowering therapies such as atorvastatin 20 mg/d plus ezetimibe 10 mg/d and atorvastatin 40 mg/d were compared in the aspect of lipid-lowering efficacy. The lipid-lowering efficacy of both strategies was in accordance with the results reported in previous studies [ 9 11 ]. Abundant evidences demonstrated that the lower the level of LDL-C reached, the better the reduction of cardiovascular events [ 12 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…CVD is multifactorial, and various risk factors that work through numerous mechanisms in the cardiovascular system affect the severity of disease risk. Statins mainly affect circulating concentrations of LDL-cholesterol, but other parameters of the lipid profile or markers of inflammation independently affect CVD progression and outcomes, such as HDL-cholesterol, LDL-cholesterol particle distribution, and elevated C-reactive protein and triglyceride concentrations [ 28 , 29 ]. The remaining risk of CVD outcomes in statin-treated patients is related to the independent effects of these risk factors and residual atherosclerosis.…”
Section: Statins: Mode Of Actionmentioning
confidence: 99%
“…However, a number of clinical trials showed 60%–70% of CVD events continue to occur despite LDL-lowering therapy, which may be due to residual risks associated with lipid abnormalities especially atherogenic dyslipidaemia, including increased TG levels and reduced HDL-C levels. 20 21 Therefore, a need for new targets to compliment the measures of LDL-C lowering has been suggested. Recent studies identified LDL-C:HDL-C ratio as a better biomarker to predict both AS progression and CVD than LDL-C or HDL-C alone.…”
Section: Introductionmentioning
confidence: 99%